Composite K/Cu/Ni hexacyanoferrates embedded biomass straw for cesium removal. (February 2023) - Li, Xiaoyu; Xiong, Yingwei; Chi, Fangting; Huang, Yumin; Wang, Zhe; Yi, Facheng
Abstract: Metal hexacyanoferrates (MHCFs) are considered to be excellent adsorbents to remove Cs(I) from radioactive wastewater. An economical and effective carrier to fix MHCFs is necessary for practical application. In this study, straw was chosen as the alternative carrier without any other modification. Two adsorbents named JG-KN and JG-KCN were obtained with the deposition of K2 Ni[Fe(CN)6 ] or K2 Cu0.8 Ni0.2 [Fe(CN)6 ] on the straw. The content of MHCFs in JG-KN was 7.3 wt% with a maximum adsorption amount (qm ) of 23.6 mg/g, and that in JG-KCN was 13.0 wt% with a qm of 51.6 mg/g. Further study of the preferred JG-KCN indicated that it had a high tolerance of pH and competitive ions, and also performed a fast adsorption rate. The fixed-bed device loaded with JG-KCN was not easy to be broken through and MHCFs were monitored to have almost no loss. The dynamic saturated adsorption amount (qdmax ) of JG-KCN was 49 mg/g. Graphical abstract: Unlabelled Image Highlights: Biomass straw was chosen as the alternative carrier of MHCFs for cesium removal. Two adsorbents named JG-KN and JG-KCN were obtained. JG-KCN has a much larger adsorption capacity than JG-KN. JG-KCN demonstrated a high tolerance of pH and ions, and a fast adsorption rate. The fixed-bed device loaded with JG-KCN was not easy to be broken through.